RANCANG BANGUN PROTOTIPE STUN-GUN DENGAN FITUR GPS SEBAGAI ALAT PERLINDUNGAN DIRI - Putra, Repson Sandy; Nurussa’adah, n/a; Zainuri, Akhmad (Jurnal Mahasiswa TEUB, 2024)
Crime has become a problem that will always be a threat to the sustainability of human life. Some examples of crimes that often occur are crimes that involve physical contact between the perpetrator and the victim, such as: kidnapping, robbery, extortion, harassment, and rape. Based on the Ministry of Women's Empowerment and Child Protection, data on violence reported until October 2023 contained 23,397 cases, of which 88% of the victims were women and 38.3% were still students. Therefore, a personal protective equipment is needed for victims of these crimes. This study aims to design a stun gun prototype that can send warning messages. The high-voltage generator module is used to produce high-voltage electrical penetration, the GPS module as a receiver module in obtaining location data, the Ngarduino.com platform as a third party in sending messages, and the ESP8266 microcontroller as a data processor and initiator for sending messages. The test results show that the high voltage generator module can produce a voltage of 13.07 kV and a current of 0.53 mA, the GPS module is able to obtain location data in under 3 minutes, the average measurement error is 7.48 meters, the average precision is 1.73 meters and the accuracy is 95.25%, and the prototype successfully sends warning messages and location addresses via the Ngarduino.com platform with a delay of 5 seconds until the message arrives. Overall, this study has succeeded in designing a stun-gun prototype tool that can send warning messages via the WhatsApp application. Keywords— Stun-gun, High Voltage, GPS, Message Sending.